Fast methods for jackknifing inequality indices - Lynn Karoly; Carsten Schröder (Kiel University, Department of Economics, 2013)
The jackknife is a resampling method that uses subsets of the original database by leaving out one observation at a time from the sample. The paper outlines a procedure to obtain jackknife estimates for several inequality indices with only a few passes through the data. The number of passes is independent of the number of observations. Hence, the method provides an efficient way to obtain standard errors of the estimators even if sample size is large. We apply our method using micro data on individual incomes for Germany and the US.
Keywords: C81; C87; D3; 330; Jackknife; Resampling; Sampling Variability; Inequality